Handbook of thermophysical properties of solid materials / Volume I. - Goldsmith, Alexander (Macmillian, 1961)
Elements (Melting temperature above 1000º F) - Iron base alloys - Cooper base alloys - Nickel base, cobalt, base and refractory metal base alloys - Light metal alloys (including Ti alloys) - Other metal alloys (melting temperature above 1000º F) - Ceramics (including glasses) - Cermets - Intermetallics - Polymeric materials (including plastics) - Composite materials